Rheumatoid Arthritis-Associated Autoimmunity Due to Aggregatibacter actinomycetemcomitans and Its Resolution With Antibiotic Therapy - Mukherjee, Amarshi; Jantsch, Vanessa; Khan, Rida; Hartung, Wolfgang; Fischer, René; Jantsch, Jonathan; Ehrenstein, Boris; Konig, Maximilian F.; Andrade, Felipe (Frontiers in Immunology, 2018)
Background:Aggregatibacter actinomycetemcomitans (Aa) is a Gram-negative coccobacillus recognized as a pathogen in periodontitis and infective endocarditis. By producing a toxin (leukotoxin A, LtxA) that triggers global hypercitrullination in neutrophils, Aa has been recently linked to rheumatoid arthritis (RA) pathogenesis. Although mechanistic and clinical association studies implicate Aa infection in the initiation of autoimmunity in RA, direct evidence in humans is lacking. Case:We describe a 59-year-old man with anti-citrullinated protein antibody (ACPA)-positive RA who presented for evaluation of refractory disease. He was found to have Aa endocarditis. Following antibiotic treatment, joint symptoms resolved and ACPAs normalized. Given the implications for RA immunopathogenesis, we further investigated the bacterial, genetic and immune factors that may have contributed to the patient's clinical and autoimmune phenotypes. Methods:DNA was extracted from serum and used to amplify the Aa leukotoxin (ltx) promoter region by PCR, which was further analyzed by Sanger sequencing. High-resolution identification of HLA alleles was performed by sequenced based typing (SBT). TNF-α, IFN-γ, GM-CSF, IL-1β, IL-6, IL-8, IL-17A, IL-18, IL-21, and IL-22 were quantified in serum by a multiplex immunoassay. IgG and IgA antibodies to Aa LtxA were assayed by ELISA. Results:Aa genotyping confirmed infection with a highly leukotoxic strain carrying a 530-bp ltx promoter deletion, shown to result in 10- to 20-fold higher bacterial expression of LtxA. Immuno-phenotyping showed high anti-LtxA antibodies, elevated cytokines implicated in RA pathogenesis (Th1/Th17), and specific host susceptibility conferred by three HLA alleles strongly linked to ACPAs and RA (DRB1*04:04, DRB1*15:01, and DPB1*04:01). One year after eradication of Aa, the patient remained free of arthritis and anti-CCP antibodies. Conclusion: In the context of genetic risk for RA, systemic subacute infection with a leukotoxic strain of Aa can drive ACPA production and a clinical phenotype similar to RA.